Piperine analogs arrest c-myc gene leading to downregulation of transcription for targeting cancer - Nirali Pandya (Nature Portfolio, 2021)
Abstract G-quadruplex (G4) structures are considered a promising therapeutic target in cancer. Since Ayurveda, Piperine has been known for its medicinal properties. Piperine shows anticancer properties by stabilizing the G4 motif present upstream of the c-myc gene. This gene belongs to a group of proto-oncogenes, and its aberrant transcription drives tumorigenesis. The transcriptional regulation of the c-myc gene is an interesting approach for anticancer drug design. The present study employed a chemical similarity approach to identify Piperine similar compounds and analyzed their interaction with cancer-associated G-quadruplex motifs. Among all Piperine analogs, PIP-2 exhibited strong selectivity, specificity, and affinity towards c-myc G4 DNA as elaborated through biophysical studies such as fluorescence emission, isothermal calorimetry, and circular dichroism. Moreover, our biophysical observations are supported by molecular dynamics analysis and cellular-based studies. Our study showed that PIP-2 showed higher toxicity against the A549 lung cancer cell line but lower toxicity towards normal HEK 293 cells, indicating increased efficacy of the drug at the cellular level. Biological evaluation assays such as TFP reporter assay, quantitative real-time PCR (qRT- PCR), and western blotting suggest that the Piperine analog-2 (PIP-2) stabilizes the G-quadruplex motif located at the promoter site of c-myc oncogene and downregulates its expression. In conclusion, Piperine analog PIP-2 may be used as anticancer therapeutics as it affects the c-myc oncogene expression via G-quadruplex mediated mechanism.